2014
DOI: 10.1093/jac/dku090
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and maintenance of multidrug-resistant Escherichia coli of canine origin harbouring a blaCMY-2-IncI1/ST65 plasmid and topoisomerase mutations

Abstract: The long-term maintenance of FQ- and ESC-resistant clones harbouring topoisomerase mutations and a blaCMY-2-IncI1/ST65 plasmid in canine commensal flora after prolonged antimicrobial use may contribute to the dissemination of multidrug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The emergence of this gene, which was pointed out in humans and animals in North and Central America in S. enterica and E. coli isolates (29), was also recently described in dogs, in the United Kingdom, the United States, and Greece (30)(31)(32). However, the proportion reported here (6.5%, ca.…”
Section: Resultssupporting
confidence: 60%
“…The emergence of this gene, which was pointed out in humans and animals in North and Central America in S. enterica and E. coli isolates (29), was also recently described in dogs, in the United Kingdom, the United States, and Greece (30)(31)(32). However, the proportion reported here (6.5%, ca.…”
Section: Resultssupporting
confidence: 60%
“…This strongly suggests an influence of this mutation for the (fluoro)quinolone resistance in E. coli . Vingopoulou et al [ 75 ] described this ParC E62K substitution previously. They detected this new amino acid exchange in enrofloxacin-resistant E. coli isolated from dog otitis and faecal samples.…”
Section: Resultsmentioning
confidence: 99%
“…Later on, VEB-6 carrying P. mirabilis were isolated from healthy horses (Schultz et al, 2017 ). In Greece, CMY-2 carried on IncI1 plasmid and harbored by ST212 E. coli strains were isolated from diseased canines in 2011 (Vingopoulou et al, 2014 ). More recently, a study conducted in Greek households revealed the detection of extended-spectrum-cephalosporin-resistant E. coli isolates.…”
Section: Distribution Of Esbls and Ampc Producers In Animalsmentioning
confidence: 99%